Effect of Lactic Acid Bacteria Strains on the Growth and Aflatoxin Production Potential of Aspergillus parasiticus, and Their Ability to Bind Aflatoxin B1, Ochratoxin A, and Zearalenone in vitro - Møller, Cleide Oliveira de Almeida; Freire, Luisa; Rosim, Roice Eliana; Margalho, Larissa Pereira; Balthazar, Celso Fasura; Franco, Larissa Tuanny; Sant’Ana, Anderson de Souza; Corassin, Carlos Humberto; Rattray, Fergal Patrick; Oliveira, Carlos Augusto Fernandes de (Frontiers in Microbiology, 2021)
The increased consumption of plant-based foods has intensified the concern related to mycotoxin intoxication. This study aimed to investigate the effect of selected lactic acid bacteria (LAB) strains on the growth of Aspergillus parasiticus NRRL 2999 and its production of aflatoxin (AF). The ability of the heat-killed (100 °C for 1 h) LAB strains to bind aflatoxin M1 (AFM1) in milk and aflatoxin B1 (AFB1), ochratoxin A (OTA) and zearalenone (ZEN) in potassium phosphate buffer (PPB) was also evaluated in vitro. Ten LAB strains were tested individually, by inoculating them simultaneously with the fungus or after incubation of the fungus for 24 or 48 h at 25 °C. Double layer yeast extract sucrose (YES) agar, de Man Rogosa and Sharpe (MRS) agar and YES broth were incubated for seven days at 25 °C to follow the development of the fungus. Levilactobacillus spp. 3QB398 and Levilactobacillus brevis 2QB422 strains were able to delay the growth of A. parasiticus in YES broth, even when these strains were inoculated 24 h after the fungus. The inhibitory effect of these LAB strains was confirmed by the reduction of fungus colony size, suggesting dominance of LAB by competition (a Lotka-Voltera effect). The production of AFB1 by A. parasiticus was inhibited when the fungus was inoculated simultaneously with Lactiplantibacillus plantarum 3QB361 or Lactiplantibacillus plantarum 3QB350. No AFB1 was found when Levilactobacillus spp. 2QB383 was present, even when the LAB was inoculated 48 h after the fungus. In binding studies, seven inactivated LAB strains were able to promote a reduction of at least 50 % the level of AFB1, OTA and ZEN. This reduction varied depending on the pH of the PPB. In milk, however, only two inactivated LAB strains were able to reduce AFM1, with a reduction of 33 and 45 % for Levilactobacillus spp. 3QB398 (Levilactobacillus spp.) and Levilactobacillus brevis 2QB422, respectively. Nevertheless, these results clearly indicate the potential of using LAB for mycotoxin reduction.